Evaluation of The Effect of Fisetin against Cyclophosphamide-Induced Myelosuppression and Oxidative Stress in Male Albino Rats - Jabbar, Amani; Alshawi, Nada Naji (Iraqi Journal of Pharmaceutical Sciences, 2023)
Myelosuppression is a serious disease that is related to the malfunction of blood cells production that leads to cytopenia which is the most serious hematologic toxicity of cancer chemotherapies including cyclophosphamide, which is a strong oxazaphosphorine [a nitrogen mustard alkylating agent] that can be used alone or combined with other chemotherapeutic agents for the treatment of different malignant diseases. It induces severe bone marrow suppression by damaging hematopoietic stem cells through the generation of oxidative stress. Fisetin is a hydrophobic polyphenolic compound with a wide range of pharmacological properties such as antioxidant, anti-inflammatory, antimicrobial, osteoprotective, antidiabetic, and anti-carcinogenic activities. The present study aims to evaluate the effects of fisetin alone and pretreatment with cyclophosphamide on some selected hematological and oxidative stress parameters in the male rats model. Animals were randomly divided into 4 groups each with 7 rats. The first group received 1% dimethyl sulfoxide (negative control group). The second group received oral fisetin. The third group received a single intraperitoneal (IP) injection of cyclophosphamide (CP) and the fourth group received fisetin for 7 constitutive days than a single IP injection of CP on day 7. Results showed that both fisetin and CP significantly reduced the total white blood cells and platelet counts compared to such counts in negative control/Group I (P<0.05) when each administered alone and in combination. Furthermore, results viewed that fisetin significantly increased GSH and SOD1, and decrease MDA levels in serum compared to such levels in CP (Group III) rats (P<0.05). The study concluded that the administration of fisetin alone causes leukopenia and thrombocytopenia and this decrease augmented in combination with CP; while exhibiting a strong antioxidant effect against CP induced-oxidative stress.